ANALISIS KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR - Mrs Muliyani (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
The loss of public trust is the biggest problem for the company. Therefore, an audit is important and expected audit results are quality. This research was conducted to analyze audit quality. So that the problem is known and produce quality audits, and companies gain trust from stake holders. The research method is quantitative with logistic regression analysis. Population is a manufacturing company listed on the IDX, a sample size of 25 firms, 7 years financial statements or 175 financial reports, and sample techniques using purposive. The results of the study showed that partially the rotation of KAP and Tenure KAP has not significant effect on audit quality. Company size has a significant effect on audit quality. Simultaneously, KAP rotation, KAP tenure and company size has significant effect on audit quality. This finding confirms that audit quality is not affected by changes in KAP, considering that KAP is the operational area of ??the company. Similarly audit tenure, the length of the company's bond with the audit committee has not effect. Because, this relationships are personal, not professional work